2012
DOI: 10.3928/01477447-20120426-14
|View full text |Cite
|
Sign up to set email alerts
|

Combined Anterior and Lateral Approaches for Bone Tumors of the Femoral Neck and Head

Abstract: Few reports in the literature describe the treatment experience of benign lesions of the femoral head and neck. Between July 2005 and August 2009, twenty-four patients with bone tumor of the femoral neck and head were treated at the authors' institution. Fourteen patients had pathological fractures of the femoral neck; in the other 10 patients, the bone cortex was involved. Average tumor size was 78 cc (range, 45-130 cc). The patients were treated by curettage plus bone grafting via an anterior approach (Smith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…There are several studies which report using internal fixation to add additional support to this precarious region. [43][44][45]…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies which report using internal fixation to add additional support to this precarious region. [43][44][45]…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the choice of surgical approach depended on the location of the lesion within the proximal femur. If the lesion involved the trochanteric or subtrochanteric region, the operation was performed through a lateral approach that provided direct access to the lesion, but if the lesion involved only the neck or head of the femur, the operation was performed through an anterior approach as this approach allowed direct access to the tumor with adequate exposure of the femoral head and neck without dislocation of the hip and complete curettage of the lesion [ 16 ]. However, this approach should be performed with caution to avoid injury of lateral circumflex femoral artery and tumor implantation around the femoral vessels [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors uses combined anterior and lateral approaches for bone tumors extending into neck and head. They reported that anterior approach allows good exposure of head for curettage than lateral approach, but there are high chances of vascular injury, contamination of femoral vessels if postoperative diagnosis was malignant bone tumor [15] . We conclude that non vascularized autologous fibular strut graft with supplementary fixation using cannulated cancellous screws is a safe and effective method of treatment for benign cystic lesions of proximal femur.…”
Section: Discussionmentioning
confidence: 99%